DIALLEL ANALYSIS OF TOLERANCE TO DROUGHT IN COWPEA GENOTYPES - Rodrigues, Erina Vitório (2017)
The low use of technologies by farmers and the occurrence of biotic and abiotic stresses are limiting factors for cowpea production in the Brazilian Northeast region. The tolerance of genotypes to drought is an alternative to decrease the negative effects of stresses on cowpea production. Thus, the objective of this work was to identify parents and combinations of cowpea genotypes with high probability of generating segregating populations with tolerance to drought. Six cowpea genotypes were crossed in a complete diallel cross design, totaling 30 F2 populations, which were evaluated together with their parents in an experiment under water deficit at the experimental field of the Embrapa Mid-North, Teresina, State of Piauí, Brazil. A triple lattice incomplete block experiment design was used, with three replications, with experimental plot consisting of six 2-m plant rows. Fifteen plants per plot were sampled to evaluate their agronomic characteristics, whose results were subjected to analysis of variance and means were used to estimate the general and specific combining abilities. The genotypes showed significant differences in all characteristics evaluated, denoting the genetic variability of the population. The additive effects were more important than the non-additive effects, and maternal inheritance was detected. The genotypes BRS Xiquexique, Pingo-de-Ouro-1-2 and MNC99-510F-16-1 were the most promising for use in recurrent selection programs for tolerance to water deficit. The hybrid combinations (1) BRS Paraguaçu X (4) CNCx-698-128G, (2) Pingo-de-Ouro-1-2 X (3) BRS Xiquexique, (3) BRS Xiquexique X (5) Santo-Inácio, (4) CNCx-698-128G X (6) MNC99-510F-16-1 and (5) Santo-Inácio X (4) CNCx-698-128G showed potential for generating superior lineages regarding bean production and tolerance to water deficit.